The impact of chronic disease diagnoses on smoking behavior change and maintenance: Evidence from China - Xinxin Chi; Xihua Liu; Cong Li; Wen Jiao (Tobacco Induced Diseases)
Introduction Managing chronic diseases and tobacco use is a formidable challenge in low- and middle-income countries (LMICs) with limited health literacy and access to quality healthcare. This study examines the empirical evidence from China, utilizing quasi-experimental approaches to assess the causal effect of chronic disease diagnoses on smoking behavior.